Vertebral anomalies in craniofacial microsomia: a retrospective analysis of 991 patients. Issue 11 (November 2018) - Renkema, R.W.; Caron, C.J.J.M.; Wolvius, E.B.; Rooijers, W.; Schipper, J.A.M.; Dunaway, D.J.; Forrest, C.R.; Koudstaal, M.J.; Padwa, B.L.
Abstract: Craniofacial microsomia (CFM) is characterized by an underdevelopment of the facial structures arising from the first and second branchial arches, but extracraniofacial anomalies such as vertebral anomalies may be present. This retrospective study was performed to determine the prevalence and types of vertebral anomalies and the association with other extracraniofacial anomalies in patients with CFM. The charts of all patients diagnosed with CFM seen in four craniofacial centres were reviewed for the presence of vertebral anomalies, symptoms, extracraniofacial anomalies, and the OMENS classification including the Pruzansky–Kaban type of mandibular deformity. A total of 991 patients were included and 28% of the patients had vertebral anomalies. The most common vertebral anomalies included scoliosis, block vertebrae, and hemivertebrae. Only 44% of the patients with vertebral anomalies had clinical symptoms; torticollis, back or neck pain, and limited neck movement were the most frequently seen. The prevalence of vertebral anomalies was greater in patients with bilateral CFM and in patients with a more severe mandibular deformity, and/or orbit, facial nerve, and/or soft tissue involvement. Patients with vertebral anomalies had significantly more extracraniofacial anomalies than patients without vertebral anomalies. Therefore, patients with vertebral anomalies should undergo cardiac, renal, and neurological evaluation.